Descriptive Cadaveric Study Comparing the Accuracy of Ultrasound Versus Fluoroscopic Guidance for First Sacral Transforaminal Injections: A Comparison Study. Issue 4 (21st September 2017) - Thompson, Bradley F.; Pingree, Matthew J.; Qu, Wenchun; Murthy, Naveen S.; Lachman, Nirusha; Hurdle, Mark Friedrich
Abstract: Background: Ultrasound is rarely used for guiding lumbosacral epidural steroid injections due to its technical limitations. For example, sonographic imaging lacks the ability to confirm epidural spread and identify vascular uptake. The perceived risk that these limitations pose to human subjects has precluded any large scale clinical trials to date. Objective: To compare the accuracy of ultrasound versus fluoroscopic guidance for first sacral transforaminal epidural injections. Design: Cadaveric comparative study using dichotomous outcomes. Setting: A fluoroscopy suite and anatomic laboratory at an academic medical center. Subjects: Four unembalmed adult human cadavers with no history of spinal surgery. Methods: Eight sites were injected twice by one interventionalist, using fluoroscopic and ultrasound guidance. In the fluoroscopy arm, contrast spread was assessed using computed tomography. In the ultrasound arm, latex spread was assessed using gross anatomic dissection. Any visible evidence of epidural spread constituted a positive result. Main Outcome Measurements: Comparison of the success of obtaining epidural contrast flow was the primary outcome measure. Secondary outcome measures included average duration, rate of intravascular uptake, and quantity of intravascular uptake. Results: All injections performed in both the ultrasound arm and the fluoroscopy arm had positive epidural spread. The average duration was 3.03 minutes with fluoroscopy and 4.76 minutes with ultrasound. The rate of intravascular uptake was 37.5% with fluoroscopy and 50% with ultrasound. Within the ultrasound arm, greater intravascular spread and duration variability were recorded. Conclusion: Although ultrasonography can provide reliable image guidance for cannulating the first sacral foramen in cadavers, it would have limited clinical utility due to its inability to visualize relevant neurovascular structures deep to the osseus roof and exclude intravascular uptake. Level of Evidence: IV